Studentsâ€™ perceptions about the importance of Group Study in the tertiary educational institutions of Bangladesh - Rahman, Md. Anisur; Humaidi, M. Nurul (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
Many things, like the normal teacher-centered learning system in Bangladesh, can be used to make the education system better, especially student-centered learning. These include peer observation, group learning, classroom observation, group supervision, and more. The main goal of this study is to find out how students in higher education institutions in Bangladesh feel about how important group research is to their academic growth in the teaching and learning system. Honors students in a college under Bangladesh National University for four years were chosen by researchers. There are both qualitative and quantitative parts to this study. To get the process done, several questions and action plans need to be carefully thought through. Group work plays a crucial role in higher education, particularly in Bangladeshi religious studies classes. Implementing this collaborative system enhances student progress and academic performance, emphasizing the need for cooperation among students, instructors, and administration to achieve educational goals and contribute to national development. Â  Banyak hal, seperti sistem pembelajaran berbasis guru yang umum digunakan di Bangladesh, dapat digunakan untuk meningkatkan sistem pendidikan, terutama pembelajaran berbasis siswa. Ini melibatkan pengamatan antar teman, pembelajaran kelompok, observasi kelas, supervisi kelompok, dan lain-lain. Tujuan utama dari penelitian ini adalah untuk mengetahui bagaimana para mahasiswa di institusi pendidikan tinggi di Bangladesh merasakan sejauh mana penelitian kelompok penting bagi perkembangan akademik mereka dalam sistem pengajaran dan pembelajaran. Para mahasiswa berprestasi di sebuah perguruan tinggi di bawah Universitas Nasional Bangladesh selama empat tahun dipilih oleh para peneliti. Penelitian ini memiliki bagian kualitatif dan kuantitatif. Untuk menyelesaikan proses ini, beberapa pertanyaan dan rencana tindakan perlu dipikirkan dengan cermat. Kerja kelompok memainkan peran penting dalam pendidikan tinggi, khususnya di kelas studi agama Bangladesh. Menerapkan sistem kolaboratif ini meningkatkan kemajuan siswa dan kinerja akademik, menekankan perlunya kerja sama antara siswa, instruktur, dan administrasi untuk mencapai tujuan pendidikan dan berkontribusi terhadap pembangunan nasional.